Entrepreneurship and Education Models of Millennial Muslim Youth in Pesantren: A Case Study on Al-Utsmani Santripreneur Indonesia - Khobir, Abdul; Sopiah, Sopiah; Adinugraha, Hendri Hermawan; Hardini, Isriani (International Journal of Social Learning (IJSL), 2024)
This research examines the education and entrepreneurship model at Santripreneur Al-Utsmani, focusing on its impact on developing entrepreneurial skills among millennial santri. Using a field research approach, this study employs descriptive and evaluative case study methods. Data collection was conducted through triangulation, including participant observation, in-depth interviews, and document analysis, with data validity ensured through triangulation and member checks. The study highlights Al-Utsmani’s entrepreneurship programs tailored to its students’ unique abilities and interests. These programs foster creativity, competence, independence, and life and career skills while integrating religious and social values. Key initiatives include cooperatives, agricultural ventures, and educational businesses that are developed collaboratively and collaboratively. Findings show that these programs significantly enhance students’ entrepreneurial spirit and contribute to their mental and economic independence, preparing them to achieve academic and religious excellence.